THE ROLE OF THE TNI NAVY’S HYDRO-OCEANOGRAPHIC CENTRE IN MANAGING SUSTAINABLE FISHERIES (A STUDY ON PROVIDING HYDROGRAPHIC DATA FOR MANAGING SUSTAINABLE FISHERY) - Anta Maulana Nasution (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2018)
Indonesia is a rich country who has many natural resources, especially marine resource. To achieve  good and sustainable marine resource management will need marine science as a tool such as hydrography. Nowaday, hydrography is often looked only for creating sea map or nautical chart for navigation. Whereas, if we look deeper about hydrography, it has a key role in fisheries resources management especially for fishermen which is hydrography can be a main support for sustainable fisheries and enhancing economic value. This paper explains about the role of hydrography in supporting economic value for fishermen and sustainable fisheries resource in installation fish aggregating devices (FADs), solving fishermen conflicts, and fisheries port. First, key role in installation FADs, effective and efficient of FADs is depend on the where FADs is installed. There are some criterias that must be considered for installing FADs such as sea depth, distance between FADs, seabed contour, free from shipping lanes, and oceanographic parameters. Those criterias needs data from Hidrography survey. Second, role of hydrography in conflict resolution by creating special map with clear coordinate points to show the boundary of fishing area that often occuring the conflict of fishermen. Third, role of hydrography to determine appropriate place for establishing fishing port. By doing hydrography survey to collect the field data in building jetty, cruise lanes, and break water port.